De la reflexión filosófica a la condensación verbo-icónica: algunos comentarios sobre el proceso de creación de la novela gráfica: Imago, el retorno de la autoconciencia - Reina Gutiérrez, Andrés (Folios, revista de la Facultad de Comunicaciones y Filología, 2023)
This writing addresses the reflection on one of the aspects of the creative process carried out during the development of the graphic novel Imago, the return of self-awareness, a research-creation work derived from the doctoral thesis Fear, self-awareness and reedom in artificial posthumanity. Creation of a graphic novel to visualize a dystopian future (Doctorate in Arts and History from the University of Granada, in 2020). The text is made up of two components. The first consists of the conceptual foundation of the project, which can be defined as a thought experiment of a reflective nature regarding a possible human future, under a dystopian perspective. And the second addresses the development of the three major phases of narrative construction of the graphic novel: 1. the literary narrative (plot and script); 2. the design of characters, settings and iconic sequentiality; and 3. the aesthetic execution itself.